Increased white matter integrity in the corpus callosum in subjects with high genetic loading for schizophrenia - Kim, Sung Nyun; Park, Jun Sung; Jang, Joon Hwan; Jung, Wi Hoon; Shim, Geumsook; Park, Hye Yoon; Hwang, Jae Yeon; Choi, Chi-Hoon; Kang, Do-Hyung; Lee, Jong-Min; Kwon, Jun Soo (Progress in neuro-psychopharmacology & biological psychiatry, 2012)
White matter abnormalities in the corpus callosum (CC) of schizophrenia have been reported to predate the illness onset. This study aimed to investigate the effect of genetic predisposition on the white matter integrity of the CC, in subjects at genetically high risk for schizophrenia (GHR) and schizophrenia patients. Fractional anisotropy (FA) of the mid-sagittal CC in 22 young GHR, 15 schizophrenia, and 26 control subjects were examined. GHR subjects were defined as non-prodromal individuals who had more than two relatives with schizophrenia within third-degree relatives, one of whom must be a first-degree relative. ANCOVA with age and gender as covariates revealed overall difference of FA in the genu and splenium among the three groups. Post-hoc analysis found significantly increased FA in the genu of GHR subjects compared to controls (corrected p<0.01), whereas schizophrenia patients showed significantly decreased FA in the splenium. The white matter change of the CC in young GHR subjects was the opposite of that in schizophrenia. To consider previous reports on FA decrease in the CC in schizophrenia and the impaired frontal functioning in GHR group, the increased FA may be an indicator of compensatory alteration in white matter integrity in young GHR people. ► GHR were genetically high risk for schizophrenia without prodromal symptoms. ► FA of the CC in GHR was significantly increased in the genu compared to controls. ► Splenial FA in schizophrenia was significantly decreased compared to controls.